Platelet-Rich Plasma Guided Injections: Clinical Application in Peripheral Neuropathies - Malahias, Michael-Alexander; Chytas, Dimitrios; Babis, George C.; Nikolaou, Vasileios S. (Frontiers in Surgery, 2014)
Platelet-Rich Plasma (PRP) is defined as an autologous concentrated preparation of platelets and their associated growth factors in a small volume of plasma. The presence of these growth factors has stimulated the scientific community to search about possible benefits of the use of PRP in tissue regeneration. Provided that previously in vitro and animal research demonstrated that PRP could probably play an important role in the treatment of neural tissue disorders, we aimed to review the current literature, regarding the clinical studies that have been conducted to confirm this hypothesis. More specifically, we have reviewed the literature concerning the clinical application of PRP in peripheral neuropathies and investigated if there is strong evidence to establish the use of PRP in clinical practice as a therapeutic option. In contrast with animal studies, we have been able to identify only few clinical data concerning the use of Platelet-Rich Plasma (PRP) in peripheral neuropathies. We found 5 trials matched to our research that have yield positive and promising results for the future for the application of PRP for the therapy of disorders of the peripheral nervous system. It is obvious that this interesting field of research gives to the scientists the ability to expand it extensively, in terms of both quality and quantity.